PELAKSANAAN DRUM-BAND DALAM KEGIATAN EKSTRAKURIKULER DI SMP NEGERI 4 SOLOK SELATAN - Resmi Agusti; Syeilendra Syeilendra; Yos Sudarman (SENDRATASIK UNP, 2013)
ABSTRAK   The research aims to describe the implementation of activity-Drum Band and the factors inhibiting the implementation of activity-Extra Drum Band at SMP 4 South Solok. This research is descriptive qualitative research. Object of study is the students of SMP 4 South Solok who participate in extracurricular activities Drum-Band. Instruments used in this study are: Primary instrument is the researcher himself as an observer (observer), participants (actors) played a role in the insider position directly in the object under study and instrument supporting documentation in the form of results from field data recording device in the form of observations, interviews and lists camera. The results describe that in terms of the location of the school and the history of the founding of the school began to get positive response from the entire community for the betterment of education for children in the future and the community with the local administration has clearly played a role in keeping the presence of schools, either directly or indirectly directly. From the research described there are two factors that affect the: factors supporting and inhibiting factors. Limiting factor is not as decisive as the contributing factors. Seen in the field supporting the dominant factor affecting the implementation of the so-Band Drum extracurricular activities can be carried out effectively and efficiently.   Keywords: Extracurricular Drum Band in SMP-4 South Solok